Human Follicle in vitro Culture Including Activation, Growth, and Maturation: A Review of Research Progress - Yang, Qiyu; Zhu, Lixia; Jin, Lei (Frontiers in Endocrinology, 2020)
Fertility preservation has received unprecedented attention nowadays. In addition to cryopreservation and re-implantation of embryos, oocytes, and ovarian tissue pieces, in vitro culture system for follicles and oocytes has been considered as an alternative strategy for fertility preservation. Since the metabolic dynamics and required nutrients are not entirely the same in different stages of follicular development, optimization of each culture step is needed. In this paper, literature regarding culture conditions in three steps were analyzed. Known additives in activation stage included 740Y-P, bpV(HOpic), follicle stimulating hormone (FSH), human serum albumin (HSA), ITS, growth differentiation factor 9 (GDF9), bone morphogenetic protein 15 (BMP15), and cyclic adenosine monophosphate (cAMP), with different degrees of activation promotion and potential detrimental effect on DNA integrity. For isolated follicles growth stage, actin A, FSH, basic fibroblast growth factor (bFGF), estradiol were proved to improve development or proliferation. As for maturation, addition of growth hormone, melatonin, C-type natriuretic peptide (CNP), GDF9, cilostamide, or forskolin helped to regulate maturation rate or improve oocyte quality. Based on previous sequential culture system for human follicles, optimization is needed to achieve higher maturation rate and better oocyte quality, pursuant to current review, which demonstrated the effects of various additives on different stages.